Glycosylated hemoglobin as an efficacious tool for early prediction of gestational diabetes mellitus - Shendre, Sneha D.; Palanisamy, Vijayalakshmi; Rewatkar, Swanand S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2021)
The incidence and prevalence of GDM is on the rise worldwide and, more so in developing countries including India. GDM is associated with maternal, fetal and neonatal morbidities. Current guidelines recommend GDM screening only at 24-28 weeks of gestation. Diagnosis of GDM in later half of pregnancy leads to fetal and maternal morbidities in spite of good glycemic control. This necessitates the use of a simpler, convenient, accurate, and reliable test, which can predict GDM in early gestation. Our article reviews the scope of using HbA1c for GDM and its efficacy in screening GDM.